Improving Numeracy Skills Through the Application of Problem Based Learning Models Assisted by Differentiated Concrete Media in Low Class Students - Rahayu, Anisa Dwi; Purwati, Panca Dewi; Trisnawati, Ismi (Journal of Primary Education, 2022)
This study aims to improve numeracy skills through the application of the Problem Based Learning (PBL) model assisted by differentiated concrete media to grade 1 student at SDN Sampangan 01 Semarang. The method used is Miles and Huberman's (1994: 12) interactive analysis method which includes three activities, namely (1) data reduction, (2) data presentation, and (3) verification, in presenting data using qualitative and quantitative data. Based on the results of research and discussion it is known that students' numeracy skills have increased by up to 82%. So, it can be concluded that the application of the PBL model with the help of differentiated concrete media can improve the numeracy skills of subtraction material in grade 1 students, because with the help of differentiated concrete media students can learn in real terms and are more interested in participating in learning.